The prognostic significance of sex and age of the child in the urinary tract infection and the formation of the nature of its course - T.V. Budnik (Počki, 2020)
Background. The study of new and management of proven risk factors for urinary tract infection (UTI) in children is of particular relevance in the current conditions of globalization of society. The purpose: to study the features of the prevalence of UTI in children, depending on the gender and age of the patient, and to assess the prognostic significance of these factors in UTI, influence on the nature of its course. Materials and methods. Two thousand six hundred and fifty-eight children with UTI aged 1 month to 18 years participated in the study. Patients’ screening and evaluation of the data were conducted with the informed consent of children, their parents, and by following the Declaration of Human Rights of Helsinki. The study design suggested the distribution of patients by gender and age. The age groups were defined as: < 1 year, 1–3, 4–6, 7–12, and 13–18 years. Statistical analysis of the dependence of the UTI on the age and gender was performed by evaluating indicators using the relative risk (RR). Results. It was found that RR of UTI in boys under 1 year of age was 2.3 times higher than in girls (2.318 ± 0.261 (1.395; 3.852) vs 0.433 ± 0.260 (0.260; 0.717), p < 0.05). In adolescence, RR of UTI in girls and boys was almost equal (1.108 ± 0.290 (0.623; 1.970) vs 0.903 ± 0.290 (0.508; 1.605), p > 0.05). The RR of chronic pyelonephritis in boys was significantly higher — by 2.4 times (2.426 ± 0.230 (1.551; 3.795) vs 0.412 ± 0.230 (0.264; 0.645), p < 0.05). Girls had 2.2 times higher RR of chronic cystitis (2.19 ± 0.43 (0.951; 5.044) vs 0.457 ± 0.430 (0.198; 1.051), p > 0.05) and 1.7 times higher — of acute pyelonephritis (1.744 ± 0.210 (1.163; 2.615) vs 0.573 ± 0.210 (0.382; 0.860), p < 0.05). In general, girls had a hundred-fold higher RR of UTI (682.382 ± 0.146 (513.003; 907.69) vs 0.001 ± 0.146 (0.001; 0.002), p < 0.05), but boys had a 1.5 times higher RR of recurrent UTI (1.526 ± 0.210 (1.018; 2.286) vs 0.655 ± 0.206 (0.437; 0.982), p < 0.05). Conclusions. Gender and age of the child as factors of influence had prognostic significance for the likelihood and relative risk of UTI, as well as for the formation of the nature of the disease.